Diagnostik Role of Marker of Cystatin C in Patient with Heart Failure - Khalilova, Feruza Abdujalolovna (Central Asian Journal of Medical and Natural Science, 2022)
The study of marker cystatin c is an impotant clinical and diagnoctical role that determines the processes of myocardial fibrosis and remodeling in the early stages of the diseases.